IMPLEMENTATION OF JUPYTER APPLICATION TO IMPROVE PHYSICS LEARNING AT UNIVERSITAS BUDI DARMA - Siti Nurhabibah Hutagalung (Edumaniora : Jurnal Pendidikan dan Humaniora, 2025)
Physics learning often faces challenges in conveying abstract and complex concepts to students. To overcome this obstacle, the use of computing-based technology can be an effective solution. One potential technology is Jupyter Notebook, a web-based application that supports a variety of programming languages such as Python. This research aims to improve the effectiveness of Basic Physics learning by implementing Jupyter Notebook in the teaching process. The methods used include training, development of teaching materials, and learning evaluation. The results showed significant improvements in concept understanding, computational skills, and student involvement in the learning process.